The wild robot - Brown, Peter, 1979- (Little, Brown and Co., 2016)
Roz the robot discovers that she is alone on a remote, wild island with no memory of where she is from or why she is there, and her only hope of survival is to try to learn about her new environment from the island's hostile inhabitants.